China's banking law and the national treatment of foreign-funded banks - Wang, Wei, 1972 September- (Ashgate, 2013)
This book assesses new developments in and reform of China's banking law system following its accession of the WTO. It focuses on the relationship between GATS/WTO national treatment obligations and China's banking law. Tracing the history of national treatment in China, the book compares the treatment of foreign-funded banks with the treatment of Chinese-funded banks and examines the structure and shortcomings of the existing banking law framework in China. This volume will be a valuable resource for academics and students as well as professionals and policy-makers working in the field of ban.